Клиничкото значење на новосоздадените анти-хла-антитела врз функцијата и хистоморфологијата на графтот кај пациенти со трансплантиран бубрег - Северова Андреевска, Галина (Медицински факултет, УКИМ, Скопје, 2018)
Transplantation is one of the best modalities for the treatment of chronic renal disease. With HLA typing and the determination of anti HLA antibodies, a new era in transplantology has opened up. Anti HLA antibodies can be directly targeted to the donor cells, the so-called "Donor-specific anti-HLA antibodies" (DSA) and cause destruction and rejection of the transplanted organ. There are other antibodies that are not DSA and can be potentially dangerous. This action causes damage to the kidney tissue, which is classified according to the Banff classification in 6 categories. Category 2 refers to antibody-related rejection (ABMR). Clinically, a rise in serum creatinine, 24 h proteinuria, and a decrease in glomerular filtration rate (GFR) can be clinically manifest. But it can also be so "Quiet" without significant disorders in the parameters of the function of the kidney. The second event was an incentive to elaborate this theme. Material and Methods: 51 patients, with a kidney transplant, with low to moderate immune risks, and non-detectable anti-HLA antibodies prior to transplantation were included. Follow-up 24 months, ambulatory according to the recommendations for monitoring transplanted patients. In all subjects, standard quadruple flow was applied: induction therapy ATG or basiliximab and maintenance therapy (corticosteroid, calcineurin inhibitor and antiproliferative drugs). Anti HLA antibodies were determined at 1.12 and 24 months of transfusion with the Luminex method for Class I, II and MICA, expressed by MFI (mean fluorescence intensity). At 12 months of the transplant, a kidney biopsy was made. The tissue was analyzed by immunofluorescence and pathohistocellular assessment, which included a classification according to the faded Banff 2013. Serum creatinine (SCr), glomerular filtration rate (GFR) and 24h proteinuria were monitored as markers of renal function. We used a standard SPS program for data processing. Results: In 12 months of transplantation, in 17 (19.60%) patients had detected anti HLA antibodies. Of all, 8 (15.68%) to Class I, 6 (11.76%) to Class II and 3 (5.88%) mixed Class I and II. The median of the average MFI for antibodies was for Class I 3228.30 ranking (876.34- 5400.23), and for Class II 3139.31 rank (983.26- 8979.51). The subjects were divided into two groups of HLA + / HLA - (17/34 patient). The groups differed in the values for sCr (<109 and> 109, p = 0.016) , 24 h proteinuria (<0.07 and> 0.07, p = 0.01) and tipe of calcineurin inhibitor (Cyclosporin/Tacrolimus, p= 0,042). In 16 patients, ABMR was found, one of which was pure and the rest were mixed with other classes. Substitution of pathohistological findings regarding the onset of anti HLA antibodies showed a significant difference in the presence of anti HLA antibodies in patients with ABMR and those without change (p = 0.042). In 11 patients, there was a worsening of the graft function, and in 6 clinically manifested rejections, treated appropriately. With linear regression analysis, the predictive factors for sCr isolated the DSA and slow graft recovery after transplantation (p = 0.001, p = 0.000), and for 24 hours proteinuria only the presence of DSA (p = 0.035). The logistic regression analysis for predictive factors in pathohistological changes identified the MFI of the antibodies> 2500 (p = 0.039)
Докторска дисертација одбранета во 2018 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Кочо Чакалароски.